2022
DOI: 10.15360/1813-9779-2022-5-18-23
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction Complicating Coronavirus Infection (Case Report)

Abstract: Coronavirus infection caused by the SARS-CoV-2 virus is a multifaceted disease due to generalized vascular endothelial damage. Endothelial damage also underlies COVID-associated coagulopathy.The paper presents a case of coagulopathy causing myocardial infarction in a 43-year-old patient with no history of coronary disease. We have reviewed the available literature for the pathophysiological rationale of the assumed possibility of coronary thrombosis resulting from coagulopathy with the intact intima of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…When comparing the frequency of the studied parameters in the groups of patients with and without thrombotic complications (Table 5), we found that patients with thrombotic complications had a longer hospital stay (11)(12)(13)(14)(15)(16) The statistically significant results are highlighted in bold. 1 Student's t-test; 2 Mann-Whitney U test, 3 Chi-square test; 4 Fisher's exact test; 5 Fisher-Freeman-Halton exact test.…”
Section: Predictors Of Thrombotic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the frequency of the studied parameters in the groups of patients with and without thrombotic complications (Table 5), we found that patients with thrombotic complications had a longer hospital stay (11)(12)(13)(14)(15)(16) The statistically significant results are highlighted in bold. 1 Student's t-test; 2 Mann-Whitney U test, 3 Chi-square test; 4 Fisher's exact test; 5 Fisher-Freeman-Halton exact test.…”
Section: Predictors Of Thrombotic Complicationsmentioning
confidence: 99%
“…Although COVID-19 is a respiratory disease and the lung is the target organ of SARS-CoV-2, extrapulmonary complications have been reported in both clinical and pathological studies. Cardiovascular, neurological, gastrointestinal, renal, hepatic, and other complications have been described [ 2 , 3 ]. Since early 2020, there have been increasing reports of hypercoagulable state, especially leading to venous thromboembolism (VTE), in patients with COVID-19 [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%